Granulocyte transfusions made with modified fluid gelatin in pediatric and adolescent patients with prolonged neutropenia. Issue 2 (15th December 2021) - Knapp, Selina; Brosig, Andreas; Troeger, Anja; Kleinschmidt, Katharina; Offner, Robert; Corbacioglu, Selim; Burkhardt, Ralph; Foell, Juergen; Ahrens, Norbert
Abstract: Background: Granulocyte transfusions (GT) are used to treat progressive systemic or local infections in prolonged neutropenic patients with antibiotic or antifungal resistance. Granulocytes are most commonly collected from whole blood by apheresis using hydroxyethyl starch (HES) as the red blood cell (RBC) sedimentation agent. This is the first study on the safety and efficacy of transfusing granulocytes collected with modified fluid gelatin (MFG) instead of HES to pediatric patients. Methods: Clinical data from 46 pediatric and adolescent patients receiving at least one MFG‐based granulocyte transfusion and in total 295 granulocyte concentrates from July 2013 to August 2019 at our local university medical center were evaluated retrospectively. Results: Forty‐one patients (89%) survived at least 21 days after their last granulocyte transfusion. These survivors had lower CRP values and higher leukocyte counts after GT than non‐survivors (mean delta of −5.34 mg/dl vs. –11.99 mg/dl and + 0.62 × 10 3 /μl vs. +0.18 × 10 3 /μl of all GT, respectively). The neutrophil corrected count increment (CCI) was 68.72 mm 2 /ml in survivors versus 28.00 mm 2 /ml in non‐survivors. There were no major or severe adverse events. Conclusion: This study suggests that modified fluid gelatin is a safe and effective alternative to hydroxyethyl starch for the collection of granulocytes for transfusion to prolonged neutropenic patients with progressive systemic or local infections refractory to antibiotic or antifungal therapy.